The Legal Validity of Sale and Purchase Deeds Executed Before a Land Deed Official (PPAT) Based on Land Statement Letters for Certified Land in Pidie Jaya Regency (International Journal of Applied Research and Innovation, 2026)
Sale and Purchase Deeds (Akta Jual Beli/AJB) constitute the principal legal instrument for registering the transfer of land rights within Indonesia's land administration system. This study examines the legal validity of AJBs executed by Land Deed Officials (PPATs) based on Land Statement Letters (Surat Keterangan Tanah/SKT) for land that has already been formally certified in Pidie Jaya Regency. An empirical juridical method was employed using statutory and socio-legal approaches. Primary data were collected through interviews with PPATs, Land Office officials, village heads (keuchik), and community members, while secondary data were obtained from legislation, legal literature, and relevant scholarly publications. The findings reveal that the continued use of SKTs is primarily influenced by limited public awareness regarding existing land certificates, weaknesses in village-level land administration, and inadequate implementation of the precautionary principle by PPATs during documentary verification. Legally, an SKT cannot replace a land certificate as the strongest evidence of registered ownership. Consequently, the practice creates legal uncertainty, weakens the evidentiary foundation of land transfer transactions, delays ownership registration, and may result in administrative liability for PPATs. Strengthening documentary verification, institutional coordination, and public legal awareness is essential to ensure legal certainty and legal protection in the transfer of registered land rights.